Educação ambiental em escolas públicas: análise das práticas pedagógicas ambientais - Gonçalves, Bruno Silva (2013)
Environmental education (EE) is shown as a dimension of the educational process that aims to build new patterns of behavior, guided by knowledge, solidarity and responsibility towards the maintenance of life on Earth. The justification for this research came from the interrogation of the existence and execution of projects or educational activities related to environmental issues and practices are continuous or sporadic public schools in João Pessoa. This research work was to analyze the existence of EE activities in two public schools, by investigating the actions of teachers through their teaching. The research was conducted with a total of 2 administrators, 13 teachers and 48 students from two classes of 6th grade of elementary school, one class from each school. The methodology we used qualitative research, observation and simple diagnostics to investigate the conceptions of teachers and students related to EE and environment. The first results showed that in state school “EEEFM Alice Carneiro” there is a neglect in structure and poor use of physical space, as in the county school “EMEF Lions Tambaú” there was a better use of space. Also identified himself, at both schools, lack of knowledge and interest by the faculty, as well as a lack of environmental issues by the student body. From these results applied to participatory research among students, with the help of teachers, with implementation of educational workshops and lectures, 10 workshops were held between the months of March to November 2012, with weekly meetings. The results showed that, with the completion of activities, one can observe changes in conceptions and attitudes toward the environment and EE, building a reflection on everyday behavior in the community where students are placed as well as at school. Finally it was found that the existing policies of EE not actually materialize, or are not accessible to managers and teachers, because schools were not identified in the study object of this research.